Analisis Perbandingan Simulasi Injeksi Plastik Terhadap Hasil Produk Dalam Software Autodesk Moldflow Pada Produk Air Filter - Zacky Fahd Mustafa; Oleh; Iwan Nugraha Gusniar (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2024)
This study aims to analyze the comparison between injection molding simulations in Autodesk Moldflow software and the products produced. Simulations are carried out to estimate the presence of production defects in objects, without having to produce the object first. In the simulation, the occurrence of production defects is estimated according to the parameters that have been entered. These production defects include short shots, flash, flowmarks, weld lines, and bubbles. In the production results, defects were found that had been predicted by previous simulations. The simulation results can be considered to be able to predict production defects that will occur in the production process.